2021
DOI: 10.1016/j.celrep.2021.109826
|View full text |Cite
|
Sign up to set email alerts
|

Laminar distribution and arbor density of two functional classes of thalamic inputs to primary visual cortex

Abstract: Highlights d DS/OS and LS axons form two major functional types of inputs from dLGN to V1 d Both DS/OS and LS boutons are distributed from superficial to middle layers in V1 d Single-axon arbors are reconstructed for DS/OS and LS axons d DS/OS axons have denser arbors in the middle layers than LS axons

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 43 publications
(70 reference statements)
0
27
1
Order By: Relevance
“…Our previous study has shown the low orientation selectivity in the LGN axons projecting to the layer 4 of V1 ( Kondo and Ohki, 2016 ), which is different from the results of other studies ( Sun et al, 2016 ; Zhuang et al, 2021 ). The reason for the discrepancy between these studies could be the differences in experimental conditions, particularly, the type of promoter used to express the genetically encoded calcium indicator protein, GCaMP6s.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Our previous study has shown the low orientation selectivity in the LGN axons projecting to the layer 4 of V1 ( Kondo and Ohki, 2016 ), which is different from the results of other studies ( Sun et al, 2016 ; Zhuang et al, 2021 ). The reason for the discrepancy between these studies could be the differences in experimental conditions, particularly, the type of promoter used to express the genetically encoded calcium indicator protein, GCaMP6s.…”
Section: Discussioncontrasting
confidence: 94%
“…One study has shown that the projecting axons in the layer 4 have lower orientation selectivity than the projecting axons in the layer 1 ( Kondo and Ohki, 2016 ). However, other studies have reported different results that thalamic axons projecting to both the layers 1 and 4 have high orientation selectivity ( Sun et al, 2016 ; Zhuang et al, 2021 ). To determine the orientation selectivity of LPN axons projecting to the different layers of V1 and compare their orientation selectivity with that of LGN axons, in vivo two-photon calcium imaging of LPN axons was conducted using GCaMP6s.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations